Detection of non-accidental injuries presenting at emergency departments. Issue 5 (25th August 2004) - McKinney, A; Lane, G; Hickey, F
Abstract : Objectives: To investigate whether cases of possible non-accidental injury as identified using five risk indicators give rise to any subjective concerns of child abuse. Methods: Questionnaires were completed by the triage nurse and attending doctor for every child attending the general hospitals of the North Western Health Board, with an injury, during a six month period. The questionnaires included an assessment of subjective concerns about the injury occurrence and five risk indicators of child abuse. Results: Children presenting with an injury who had two or more positive indicators failed to raise subjective concerns in the attending emergency department staff. Conclusions: The introduction of a policy of identifying positive indicators from the five risk indicators of child abuse needs additional computer support within emergency departments.